Interaction Between Social Acceptance and Humanistic Green Techno Educational Capability in Supporting Environmentally Friendly Solar Energy Investments in Jember District - Auliq, Muhammad A'an; Sularso, Raden Andi; Safitri, Julia; Isnarno, Endi (Indonesian Journal of Business Analytics, 2023)
The development of a dynamic energy system requires adjustments to energy policies that are in line with and receive strong support from human resources in government and society. One of the most effective and sustainable policies is encouraging investment in environmentally friendly infrastructure, such as renewable energy. The potential of solar energy, which is a renewable energy source, offers a solution to the energy crisis experienced by developing countries. In this research, a new concept is proposed which is known as "the interaction between social acceptance and investment readiness (SONVES) as a mediator of green_ Techno Humanistic Education Capability towards solar PV investment readiness". This aims to determine the effect of increasing social acceptance, technology acceptance, environmental awareness, and economic value which are expected to have a positive effect on investment readiness. This research model uses a quantitative descriptive approach to describe the situation objectively using data in the form of numbers.   overall investment readiness.